Empowering infants through responsive and intentional play activities. Issue 2 (3rd April 2017) - Shin, Minsun; Partyka, Thomas
ABSTRACT: This qualitative case study explored how an infant teacher provided meaningful learning experiences for infants through play and the teacher's educational rationale behind these experiences. Findings were based on multiple sources of data, including classroom observations (natural observation and videotaped observation) for approximately 12 weeks and a teacher interview. The findings confirmed that infant play is critical for infant learning and development and portrayed the process through which the infant teacher created play spaces for infants and supported infants' play through both pre-planned, teacher-directed, intentional activities, and child-initiated, emerging play activities. Our study highlighted that the designing of infant play and the learning process needs to be flexible and based on careful observation and reflection in order to meet the rapidly changing needs and interests of a group of infants as well as individual infants.